Optimasi Penjadwalan Rapat Berbasis Web Untuk Mengurangi Konflik Jadwal Menggunakan Kombinasi Algoritma Greedy dan Decision Tree - Ahmad, Tjoet Muty; Lamasitudju, Chairunnisa Ar. (Jurnal Algoritma, 2025)
The manual meeting scheduling process has a high potential for scheduling conflicts. These conflicts include delays in information, meeting room clashes, or meeting time clashes. These problems are caused by the absence of a system and visualization for managing meeting schedules. To streamline the scheduling process, a website-based meeting scheduling information system was developed for activities that are carried out routinely with high frequency, using a combination of two algorithms that can overcome these problems. The Greedy algorithm is used to detect conflicts, and the rule-based Decision Tree algorithm is used to provide alternative time or room suggestions when schedule conflicts occur. The results of blackbox testing and usability testing prove that the application of these algorithms makes the system more effective and provides the right workflow for this system. This research contributes to the development of an effective meeting scheduling system and integrates two algorithms as a new solution in managing the scheduling process.